Translation and cross-cultural adaptation of heat strain score index (HSSI) into the Malay language - Mei Ching Lim; Khamisah Awang Lukman; Nelbon Giloi; Mohammad Saffree Jeffree; Saihpudin Sahipudin Saupin; Zulkhairul Naim Sidek; Mohd Nazri Mohd Daud; Glynn Dexter Andreas (PLoS ONE, 2023)
Concerns about the health and safety of working populations as well as preventive actions to reduce heat-related illnesses and fatalities have intensified as global warming and heatwaves continue to rise as a result of climate change. This study aimed to translate and culturally-adapted the translated Malay version of the Heat Strain Score Index (HSSI) questionnaire so that it can be utilized as a screening tool for heat stress among the Malay-speaking outdoor workers. The original English version of HSSI underwent forward-backward translation and was cross-culturally adapted into the Malay language by bilingual translators based on established guidelines. The content validation was reviewed by a six-member expert committee including the representative of outdoor workers. Face validation was carried out among 10 outdoor workers involved with various work tasks. Psychometric analysis was conducted based on a cross-sectional study among 188 workers who were eligible. Exploratory Factor Analysis (EFA) was used for construct validity while internal consistency reliability was performed using Cronbach’s alpha. The interclass correlation coefficient (ICC) was used to calculate the test-retest reliability. Both content and face validity were acceptable with the overall content validity index being 1.00, while the universal face validity index was 0.83. The factor analysis using varimax rotation extracted four factors which explained 56.32% of the cumulative percentage of variance and factor loading ranging from 0.415 to 0.804. The internal consistency reliability was acceptable with Cronbach’s alpha ranging from 0.705 to 0.758 for all the factors. The overall ICC value was 0.792 (95% CI; 0.764–0.801) which signifies good reliability. The findings from this study indicate that the Malay version of HSSI is a reliable and culturally-adapted instrument. Further validation is needed so that it can be used extensively assess the heat stress among susceptible Malay-speaking outdoor workers in Malaysia who are exposed to hot humid environments.